RELASI AKAL DAN WAHYU DALAM PEMBENTUKAN HUKUM ISLAM: SUATU KAJIAN FILSAFAT HUKUM ISLAM - Zaleha Zaleha; Effinda Harahap; Ade Ilham; Rahmayani Nasution; Fitri Ramadhan (Jurnal Ilmiah Advokasi, 2025)
This study explores the relationship between reason (ʿaql) and revelation (waḥy) in the formation of Islamic law from the perspective of Islamic legal philosophy, with particular attention to its epistemological foundations. The study starts from the premise that revelation constitutes the highest normative authority in Islamic law, while reason serves as a rational tool through which divine guidance is understood, interpreted, and applied within changing social contexts. Drawing on textualist, rationalist, and integrative approaches developed by classical and contemporary Muslim legal thinkers, this research employs a library-based method with a philosophical and analytical approach to both primary and secondary sources of Islamic law. The findings indicate that a harmonious interaction between reason and revelation gives rise to a more adaptive and balanced methodology of ijtihād, one that remains faithful to the normative authority of revelation while effectively addressing contemporary legal challenges in a manner that is proportionate, context-sensitive, and oriented toward human well-being.Keywords: Reason and Revelation; Islamic Legal Philosophy; Epistemology of Islamic Law; Ijtihād; Maqāṣid al-Sharīʿah.